Evaluating the Efficacy of Gum Arabic-Zinc Oxide Nanoparticles Composite Coating on Shelf-Life Extension of Mandarins (cv. Kinnow) - Nxumalo, Kwanele Andy; Fawole, Olaniyi Amos; Oluwafemi, Oluwatobi Samuel (Frontiers in Plant Science, 2022)
Restricted postharvest application of synthetic fungicides in maintaining the quality of citrus fruits has led to a search for alternative postharvest treatments. This study evaluated the efficacy of gum arabic (GA) enriched with green synthesized zinc oxide nanoparticles (ZnO-NPs) in maintaining the postharvest quality of mandarin (cv. Kinnow). ZnO-NPs were synthesized using Bidens pilosa leaf extract and incorporated into GA (2% w/v) at 0, 0.25, 0.5, and 1% to form composite coatings: GA, GA + ZnO-NP 0.25%, GA + ZnO-NP 0.5% and GA + ZnO-NP 1%, respectively. Fruit were dipped for 3 min in the respective coatings, with untreated fruit used as control. Fruit were air-dried, packed in commercial cartons, and stored at 5 ± 1°C and 90 ± 5% relative humidity (RH) for 40 days and observed at 10 days intervals, plus 5 days at 20 ± 5°C and 65 ± 5% RH to determine the incidence of physiological disorders. GA + ZnO-NP showed promise as an alternative postharvest treatment for controlling postharvest physiological disorders associated with ‘Kinnow’ mandarin. For instance, GA + ZnO-NP 0.5% markedly minimized weight loss (9.2%), electrolyte leakage (43.8%) and chilling injury incidence (5.4%) compared to control (weight loss; 33.3%, electrolyte leakage; 90.3% and chilling injury incidence; 41.5%) at the end of the storage. GA + ZnO-NP 1% significantly alleviated rind pitting, with 13.2% incidence compared to 45.2% rind pitting incidence in the control fruit. This was due to significantly higher phytochemical and antioxidant capacity and reduced antioxidant enzyme degradation in coated fruit than in control. In conclusion, gum arabic coating enriched with ZnO-NPs at concentrations between 0.5 and 1% is recommended as a viable option to maintain the quality of ‘Kinnow’ mandarin fruit during cold storage.